Deconstructing Andrei Tarkovsky’s Magic Realism: Sound Design and the Category of Irreal - Shpinitskaya, Julia (Sens public)

(untitled) (Département des littératures de langue française, 2019)
Rejecting the common practice of his time, Andrei Tarkovsky challenged the composer Edward Artemiev to create unprecedented sound design for his films in the place of conventional musical soundtracks. He also followed this path in his later films produced without Artemiev. This article analyzes the audio-visual sequences of Tarkovsky’s films from the 1970s and the 1980s, exploring transitions from real mode to magic mode, as well as the role of sound design in these cinematic shifts. The new technology and the novel electronic sound that influenced creative processes are at the heart of this analysis. Unique media, such as the ANS and Synthi 100 synthesizers that became available for Artemiev, were key factors that motivated his original sound work. They allowed him to create a sound space capable of absorbing divergent sources (natural sounds, noises, acoustic instruments, and musical quotations), and triggering off transformation of the initial sound sources into sounds of ambiguous nature. This analysis recreates the process of sound-making from its conceptual origins to its final representations, interpreted through comments by Edward Artemiev and Owe Svensson (a Swedish sound-mixer, who worked with Tarkovsky on his last film, The Sacrifice).